2013
DOI: 10.1148/radiol.13121232
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Offers an Option for Safe and Effective Sedation for Nuclear Medicine Imaging in Children

Abstract: DEX offers advantages for pediatric sedation for nuclear medicine imaging. DEX produces a condition similar to natural sleep, with no detrimental effect on respiration. The hemodynamic variability anticipated with DEX did not require pharmacologic treatment, and the drug was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 38 publications
(55 reference statements)
3
36
1
2
Order By: Relevance
“…Many studies have revealed that the sedative dose of DEX can create a state of natural sleep and it can be safely used in children without inducing respiratory depression [20]. Intranasal DEX is relatively easy and convenient, and it also reduces first-pass metabolism and has been successfully used for sedation [11].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed that the sedative dose of DEX can create a state of natural sleep and it can be safely used in children without inducing respiratory depression [20]. Intranasal DEX is relatively easy and convenient, and it also reduces first-pass metabolism and has been successfully used for sedation [11].…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] It has been successfully administered via the IV and intramuscular routes for pediatric radiologic imaging. 7,[16][17][18] To date, however, the literature does not describe sedation via the intranasal route with aerosolized DEX for pediatric CT. 5,16 The intranasal route has been described for perioperative anxiolysis. [19][20][21][22] In adults, there is up to 83% bioavailability of intranasal DEX, with onset in 30-45 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…On arrival at the PACU, vital signs (HR, non-invasive blood pressure, RR, SpO 2 , temperature), RSS, and VAS were monitored every 5 min for the first 20 min, then every 10 min for the rest of the time until the patients were discharged to the wards (Aldrete Score ≥ 9) (Mason et al, 2013). Surgeon satisfaction was assessed as follows 24 h after burr-hole surgery: 1, extremely dissatisfied; 2, not satisfied but able to manage; 3, satisfied; 4, extremely satisfied); patients were visited to assess satisfaction on a 7-point Likert verbal rating scale (Bagchi et al, 2014).…”
Section: Methodsmentioning
confidence: 99%